A Hospital-Based Analytical Study on Antibiotic Utilization in Pediatric Patients and Antibiotic Stewardship - Mahbubur Rahman; Sanjoy Chungkrang; Anta Sharma; Kritika Sharma; Arfa Khan (Journal of Pharmacy and Bioallied Sciences)
Background: Antibiotics are prescribed frequently for children, and it has been discovered that nearly half of all antibiotics prescribed in pediatric healthcare settings are deemed inappropriate. This misuse of antibiotics leads to the rise of antimicrobial resistance, adverse drug reactions, increased morbidity, and higher hospitalization costs. If no global measures are implemented, it is estimated that antimicrobial resistance will cause 10 million deaths by 2050. Objective: The objective of this study is to analyze the antibiotics utilization patterns in the pediatric department for the upliftment in the adherence to the guidelines while prescribing in the hospital. Approach: It is a prospective observational cross-sectional study. Data of 152 patients hospitalized in the in-patient department and pediatric intensive care unit were taken for a period of 6 months. All the data were collected and designed in sheets and input into Microsoft Excel 2014, and figures and tables are presented. Results: The maximum number of patients (36%) receiving antibiotics fall in the 11–14 age group of years and received prescriptions of ceftriaxone only or in combination with other antibiotics to the maximum (50.7%) in hospitalized pediatric patients, with gastrointestinal system complications being the most commonly treated. 41.4% patients were on a single antibiotic. Conclusion: With an average of 1.8 antibiotics per patient, gastrointestinal system complications were the most commonly treated and the most common cause of hospitalization, whereas third-generation cephalosporins were prescribed mostly among pediatric patients admitted in the hospital. There is necessity of assessment of Improper Prescription Practices for Children to Inform Pediatric Antibiotic Stewardship and prevention of empirical therapy, antibiotic resistance, and associated negative impacts on health outcomes further.